Emphysema severity index (ESI) associated with respiratory death in a large Swedish general population. (August 2022) - Luoto, Johannes; Pihlsgård, Mats; Pistolesi, Massimo; Paoletti, Matteo; Occhipinti, Mariaelena; Wollmer, Per; Elmståhl, Sölve
Abstract: Recently, it has been shown and validated that presence and severity of emphysema on computed tomography could be estimated by a novel spirometry based index, the emphysema severity index (ESI). However, the clinical relevance of the index has not been established. We conducted cox-regression analyses with adjustment for age, smoking, sex, forced expiratory volume in 1 s (FEV1 ) and forced vital capacity (FVC) to study whether ESI was associated with all-cause, respiratory and non-respiratory 10-year mortality. Study population was all participants with acceptable spirometry from the Gott Åldrande i Skåne study, a Swedish general population aged 65–102 years old. ESI is expressed as a continuous numeric parameter on a scale ranging from 0 to 10. Out of the 4453 participants in the main study, 3974 was included in the final analysis. Higher age, higher ESI, lower FEV1 and male sex increased hazard of respiratory death. ESI was significantly correlated to respiratory death but not non-respiratory death, while high age, male sex and low FEV1 was associated with non-respiratory as well as respiratory death. Current smoking habits increased the hazard of respiratory death but did not reach significance (p 0.066) One unit increase in ESI increased hazard of all-cause death by 20% (p 0.0002) and hazard of respiratory death by 57% (p < 0.0001). The ESI is a novel clinical marker of emphysema severity that is associated with respiratory death specifically. Since it can be derived from standard spirometry there are potential benefits for clinical practice in terms of more individualised prognosis and treatment alternatives. Highlights: Emphysema Severity index (ESI) is a novel index available from standard spirometry. ESI is associated with respiratory death. ESI is a potentially useful marker in clinical practice as well as treatment studies.